DC and low-frequency noise characteristics of GaN-based HEMTs under cryogenic temperatures. (27th October 2022) - Zeng, Bolun; Zhang, Haochen; Luo, Chao; Xiang, Zikun; Zhang, Yuanke; Wen, Mingjie; Xue, Qiwen; Hu, Sirui; Sun, Yue; Yang, Lei; Sun, Haiding; Guo, Guoping
Abstract: In this work, the device characteristics of GaN-based high-electron-mobility transistors (HEMTs) were systematically investigated by the direct current (DC) and low-frequency noise (LFN) measurements within the temperature ranging from 300 K to 4.2 K. The temperature-dependent behavior of the on- and off-state electrical properties was statistically analyzed, highlighting an overall improved device performance under cryogenic temperatures. In addition, the LFN of the device exhibited an evident behavior of 1/ f noise from 10 Hz to 10 kHz in the measured temperature range and can be well described by the carrier number fluctuations with correlated mobility fluctuations (CNF/CMF) model down to 4.2 K. Based on this model, we further extracted and discussed the defect-related behavior in the devices under low-temperature environments. These experimental results provide insights into the device characteristics of GaN-based HEMTs under cryogenic environments, motivating further studies into the GaN-based cryo-devices and systems.